Paddy Field Conversion in Malaysia : Issues and Challenges - Muhammad Yasar; Chamhuri Siwar (Department of Agricultural Engineering, Syiah Kuala University, 2016)
Abstract. The diminishing of paddy field due to land use conversion to non-agricultural or non-paddy agricultural purpose is a serious threat to national food security prospect. This present study intends to explain the phenomena of diminishing paddy field range in Malaysia. This is a descriptive correlation study. The result of the study found that the size of paddy field in Peninsular Malaysia either according to the state or the granary area was diminished. According to the state, the size of paddy field has reduced by 88,321 ha (22.17%) in the last 15 years or equivalent to 1.49% per year. Whereas, according to granary area, the size of the paddy field has reduced by 10,790 ha (5.10%) or equivalent to 0.34% per year. The diminishing of the size of the paddy field indicates a significant correlation to the national paddy production. In the meantime, the population growth is expected to increase whilst productivity expands slowly. The government needs to emphassion this matter to attain the goal of food security. Konversi Lahan Sawah di Malaysia : Isu dan Tantangan Abstrak. Berkurangnya lahan sawah karena konversi penggunaan tanah ke non-pertanian atau tujuan lain yang bukan lahan padi merupakan ancaman serius bagi prospek ketahanan pangan nasional. Penelitian ini bertujuan untuk menjelaskan fenomena berkurangnya lahan sawah di Malaysia. Hasil penelitian ini menemukan bahwa ukuran sawah di Peninsular Malaysia juga daerah lainnya atau lokasi pusat padi/lumbung juga berkurang. Berdasarkan data nasional penurunan luas lahan sebesar 88,321 ha (22,17 %) untuk 15 tahun terakhir atau setara dengan 1,49 % per tahun. Sedangkan pada daerah lumbung, luas sawah telah mengalami pengurangan sebesar 10,790 ha (5.10 %) atau setara dengan 0,34 % per tahun. Berkurangnya lahan sawah ini terindikasi adanya korelasi yang signifikan untuk kondisi produksi padi secara nasional. Sementara itu , pertumbuhan penduduk diperkirakan terus meningkat pada saat produktivitas padi mengalami pertumbuhan dengan lambat. Pemerintah perlu mengendalikan hal ini untuk mencapai tujuan ketahanan pangan nasionalnya.